Challenges on Rural Area Management: Investigating the Relationship between Rural Development and European Funds - ȚENEA, Lili (Journal of Advanced Research in Management; Vol 12 No 1 (2021): JARM Volume XII Issue 1 (23) Summer 2021DO - 10.14505//jarm.v12.1(23).03, 2021)
The economic activity, in most of the rural places is focused on agricultural practices. Only in the developed settlements situated in the expansion area of the important towns there is a viable entrepreneurial activity, stimulating the community and offering it lucrative opportunities for the inhabitants, although most of the rural settlements do not manage to overcome the underdevelopment stage in which they are. Only in the case of the significant rural settlements showing an interest in investments for the relocated production facilities in the towns, we can talk about intense economic activities. These cases are isolated and most of the times, these settlements do not match the classic portrait of the rural settlements being more like the towns. That is why the developed rural settlements are economically and socially connected to the town around which they gravitate, as opposed to the case of the traditional rural settlements. Looking at the situation of the social and economic life registered on the level of the rural population and considering the most probable evolution trends on a medium and long term, we identified a series of challenges where it is compulsory to involve the public or the private organizations from the field.